A community for students.
Here's the question you clicked on:
← 55 members online
 0 viewing
Fedorable
 one year ago
Use a transformation to solve the equation.
h + (–3) = –0.6
A.
h = –3.6
B.
h = –2.4
C.
h = 2.4
D.
h = 3.6
Fedorable
 one year ago
Use a transformation to solve the equation. h + (–3) = –0.6 A. h = –3.6 B. h = –2.4 C. h = 2.4 D. h = 3.6

This Question is Closed

vheah
 one year ago
Best ResponseYou've already chosen the best response.0Since you have a 3 and you want to isolate h by itself, you have to alter the sign and add 3 to both sides: h= 3+(0.6) a positive sign * a negative sign = negative h= 30.6 h=2.4
Ask your own question
Sign UpFind more explanations on OpenStudy
Your question is ready. Sign up for free to start getting answers.
spraguer
(Moderator)
5
→ View Detailed Profile
is replying to Can someone tell me what button the professor is hitting...
23
 Teamwork 19 Teammate
 Problem Solving 19 Hero
 Engagement 19 Mad Hatter
 You have blocked this person.
 ✔ You're a fan Checking fan status...
Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.